Structural Relationship between Social Benefit, Dependency, Satisfaction, and Habit Formation on the Use of Social Media - Singgih Santoso; Budi Sutedjo Dharma Oetomo (Binus Business Review, 2019)
The main objective of the research was to investigate whether a consumers’ habit formation was influenced by the satisfaction they got because of the social benefit and dependency on the use of social media. The research design used survey methods with questionnaires for 100 respondents. The researchers employed Structural Equation Models (SEM) with AMOS software to test the research model. From consumer’s profiles, the results show that the most widely used types of social media are Line and Instagram. Most consumers use more than three hours every day to access social media to do tasks and chat. In testing the relationship between variables in the research model, the results show that dependency has a positive effect on satisfaction, but the social benefit does not. Moreover, satisfaction has a positive effect on habit formation. Those results show that consumer behavior through social media can be strengthened by increasing product satisfaction and the intense use of social media. Hence, the findings of this research may give insights to the marketer to use social media as a product quality promotion media.